Keanekaragaman Serangga Hama dan Musuh Alami pada Tanaman Buncis (Phaseolus Vulgaris L.) di Desa Cumbi, Kecamatan Ruteng, Kabupaten Manggarai - Emanuel Teka; Yasinta L Kleden; Agustina E Nahas; Rika Ludji (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
This research aims to determine the diversity of insect pests and natural enemies on bean plants (Phaseolus vulgaris L.) in Cumbi Village, Ruteng Subdistrict, Manggarai Regency from April to May 2023. The method method used in this research is survey method with direct observation technique on bean plants and sampling from various traps. sampling of various traps. The types of traps used in this study were (yellow sticky traps), (pitfall traps) and (swepnet traps). Observations were made every week starting from plant one week after planting until harvest. Insects found in the field were identified at the Plant Pest Laboratory, Faculty of Agriculture, Nusa Cendana University. The results of the study found 5 species of insect pests on bean plants, namely Oxya chinensis, Locustana pardalina, Malacosoma americanum, Stethorus picipes and Planococcus citri; and 3 species of natural enemies, namely Podisus maculiventris, Arikus cristatus and Calliphora vomitoria. The diversity of insect pests on bean plants in the research location is categorized as medium with an index value of 1.56451 and the diversity of natural enemies is categorized as low with an index value of 1.09281.